Determination of Radiochemical Purity and Pharmacokinetic Parameters of 99mTc-Sulphur Colloid and 99mTc-Tin Colloid - Jovanović, V.; Konstantinovska, D.; Milivojević, K.; Bzenić, J. (Nuklearmedizin - NuclearMedicine, 1981)
Labelling yield and radiochemical purity, higher than 95%, of 99mTc-colloid preparations were determined by using the paper chromatography method. Less than 3% of labelled citric acid, added to the preparation as a buffer solution, has been found in 99mTc-sulphur colloid. High radiochemical purity and optimum size of colloid particles has also been proved by biodistribution studies on experimental animals. The analysis performed has shown that more than 50% of 99mTc-colloid preparations excreted by urine is 99mTcO–, the remaining past 50% being protein bound 99mTc. Biological half-time of excretion of the fast phase is the same for both preparations, i.e. 10 min, while for the slow component it is 120 min in 99mTc-S-colloid and 160 min in 99mTc-Sn colloid.